How Capital Structure And Financial Performance Impact On Food And Beverage Company Value? - Alfisah, Erni; Kurniaty; Rizka Zulfikar (International Journal of Science, Technology & Management, 2022)
The purpose of this study is to examine and explain the effect of capital structure on firm value, the effect of capital structure on financial performance, the effect of financial performance on firm value, the effect of capital structure and financial performance simultaneously on firm value. This study used Food Beverage company that listed in Indonesia Stock Exchange (IDX) on period 2016 – 2020. The model used in data analysis in this study is a simple multiple regression model because the measurement of the dependent and independent variables in this study is in the form of numbers with size scales and more than one independent variable. The results of the study show that: 1) Capital structure has no significant effect on firm value; 2) Capital structure has no significant effect on Financial Performance; 3) Financial Performance has a significant effect on Firm Value; 4) Capital Structure and Financial Performance simultaneously have a significant effect on firm value. The Determination Test (R2) produced is 0.331 (33.1%), meaning that the contribution of the variable influence of Capital Structure and Financial Performance to Firm Value is 33.1%, while the remaining 66.9% is influenced by other variables not examined in this study.